Impact of Technostress and Academic Self-Efficacy on Students’ Perceived Academic Performance - Parviainen, Anna-Maria (2025)
The continually increasing integration of IT into education has many positive implications, but due to technostress, it can also have a negative influence on students’ wellbeing and their academic performance. At the same time, self-efficacy affects the amount of stress people experience and increases performance. However, previous research on the combination of these factors and their mutual influence on academic performance is scarce, and the effect academic self-efficacy has on different techno-stressors has remained unexamined. To address this gap, this study examined whether students experience technostress when using IT in their studies, how technostress influences students’ perceived academic performance, and whether academic self-efficacy affects students’ experience of technostress and the perception students have of their academic performance. The data collected through an online survey from 97 participants among the students at the University of Jyväskylä was analysed with several quantitative methods. The results indicate that students experience low to moderate amounts of technostress, and that technostress induces strain among students, which decreases their perceived academic performance. Specifically, techno-stressors techno-complexity and work overload increased strain and decreased perceived performance. The results also indicate that academic self-efficacy has major impacts on students’ technostress and performance. Academic self-efficacy was found to increase perceived performance while also decreasing the strain caused by technostress, as well as decreasing several techno-stressors directly. The findings suggest that students’ academic performance could be increased not only by alleviating or mitigating technostress but also by facilitating the development and increase of students’ academic self-efficacy. The implications of the results highlight the importance of adopting more practical and less complex IT in educational institutes while also providing adequate training in the use of IT. However, further research is needed to understand and clarify the complex relationships among the different factors that affect academic performance and student wellbeing.